Vince Flynn Denied access - Bentley, Don; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel, 2025)
"The Central Intelligence Agency is in crisis. Following the collapse of the Soviet Union, Congress is questioning the organization's necessity. Interim CIA director Thomas Stansfield must fight for his agency's survival while explaining why the previous candidate for his job was found murdered in a French hotel -- surrounded by booze, cash, and dead men. Worst yet, a brilliantly run sting operation in Moscow has resulted in the arrest of America's most prized Russian asset and the expulsion of his CIA handler. With the CIA's Moscow Station now paralyzed by the catastrophic intelligence failure, Stansfield seeks help from Mitch Rapp, a newly minted assassin in the secretive Orion program. But Rapp has problems of his own: when his Swiss girlfriend Greta's grandfather receives a box containing the head of a former Cold War comrade along with a note promising that Greta's head will be next, Rapp finds himself on the frontlines in a war between the American and Russian intelligence services. To protect the woman he loves and save the CIA from destruction, Rapp must be willing to risk everything." --